Library Workers’ Perceptions of Immigrant Acculturation: Renewed Understandings for Changing Contexts - Ndumu, Ana; Park, Hayley; Siebold, Connie (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2025)
Objective – Immigrants’ adjustment to U.S. society, also known as immigrant acculturation, is a vast area of study, but there are few studies relating to immigrant acculturation within the library and information science field.Methods – Data from 131 survey responses and 20 interviews suggest that library workers are somewhat familiar with the immigrant acculturation process, but specific and evidence based training can further their knowledge.Results – Insight on immigrant acculturation contextualizes immigrants’ realities and thus assists library workers in being aware of and responsive to the nuances of adjusting to and thriving in a new country like the U.S.Conclusion – In the face of anti-immigration legislation and heightened xenophobic misinformation, librarians need professional development drawn from empirical investigations of immigrants’ acculturative experiences.